The Return of Alexander the Great in the Third Century A.D.: a Question of Daimones and Physical Immortality - Endsjø, Dag Øistein (Classica et Mediaevalia, 2022)
Why was an unknown man insisting he was Alexander the Great received with distinct deference by Roman officials and Bacchic celebration by hundreds of attendants around A.D. 221? Examining Dio Cassius’s presentation in light of contemporary beliefs, one finds that the enthusiastic reception most probably was due to the con-viction that Alexander had actually returned physically immortal and deified, either resurrected or never having died at all. The respectful awe of the officials was also most likely caused by either this belief or by their holding that this was the dead and disembodied hērōs of the famed conqueror.